1997
DOI: 10.1111/j.1600-0714.1997.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of Fas antigen in oral epithelia

Abstract: A monospecific and high titer polyclonal antibody, designated as Fas D, raised against synthetic polypeptides selected from a part of the human Fas antigen (aa 104-114), was used to identify the Fas antigen in human oral epithelia in normal and pathological states. The human gingival proteins had been extracted and analysed by an ABC (avidin-biotin complex) immunoblotting technique. The antibody interacted with a single band in gingival proteins with an estimated molecular weight of 35,000, which is in good ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…In contrast to the present results, the authors found that Fas, FasL and caspase-3 reactivity in peripheral columnar or cuboidal cells was more intense than that in central polyhedral cells; this requires further study. MURAKI et al 16 demonstrated in their study that Fas-positive cells were found in leukoplakia with keratosis and in well-differentiated squamous cell carcinoma, suggesting that the Fas antigen may be related to the keratinization of some types of lesions. Taken together with the present results, the expression of both Fas and FasL in ameloblastomas appears to be associated with certain features of differentiation or degeneration of tumour cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to the present results, the authors found that Fas, FasL and caspase-3 reactivity in peripheral columnar or cuboidal cells was more intense than that in central polyhedral cells; this requires further study. MURAKI et al 16 demonstrated in their study that Fas-positive cells were found in leukoplakia with keratosis and in well-differentiated squamous cell carcinoma, suggesting that the Fas antigen may be related to the keratinization of some types of lesions. Taken together with the present results, the expression of both Fas and FasL in ameloblastomas appears to be associated with certain features of differentiation or degeneration of tumour cells.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have detected apoptotic cells and several apoptosis-related proteins, such as Bcl-2 family gene products, Fas, Fas-ligand (FasL) and caspase-3, in developing tooth germs, odontogenic keratocysts and ameloblastomas 4,[6][7][8][9]14,16,19 , suggesting that apoptosis may play important roles in normal odontogenesis as well as in the pathogenesis of odontogenic lesions. The aim of this study was to evaluate the expression pattern of apoptosis-related proteins in different histological subtypes and various cellular components of ameloblastomas.…”
mentioning
confidence: 99%
“…20 Previously, it has been shown that squamous cell carcinomas of the tongue and oral cavity, lung, and squamous cell carcinoma cell lines express Fas. [21][22][23][24] In a recent study, however, Fas expression in ESCCA was found to be heterogeneous and essentially absent in the majority of cases, although it was expressed in the Immunoperoxidase staining was done with hematoxylin counterstaining (original magnification ϫ100).…”
Section: Discussionmentioning
confidence: 99%
“…Derangement of the CD95 system is critical for tissue damage of UV-radiated skin and for dermic injury originating from cutaneous lupus erythematodes (Nakajima et al, 1997). In contrast to malignant melanoma and basal cell epithelioma, CD95 receptor expression was present in squamous cell carcinoma (SCC) as well as in normal skin (Muraki et al, 1997). High levels of CD95L expression were typically observed during tumor progression and immune evasion of malignant melanoma (Hahne et al, 1996).…”
mentioning
confidence: 97%